PELAKSANAAN DISTRIBUSI BERAS UNTUK KELUARGA MISKIN DI KELURAHAN BANSIR DARAT - Sri Wahyuni E.21109077 (FISIP Universitas Tanjungpura, 2013)
The problem in this study is the distribution of Raskin in the Village Bansir Land , District East Pontianak , Pontianak not on target . Besides, the data RTS PM needs to be reviewed because it does not correspond to the expected allotment policy Raskin program . Another problem is the program Raskin less professional and more dominant element of nepotism in its implementation . The results showed that the implementation of the program in the Village Bansir Army Raskin is not maximized , it is based on field research findings which found irregularities in their distribution . Deviations in question is related to the determination of Target Households Beneficiaries there are still poor families who have not been recorded and registered as Beneficiaries Target Households and families otherwise there among the better but listed as Target Households Beneficiaries . Responding to a phenomenon that there would have to be raised synergistic coordination of policy makers and program implementers Raskin to avoid deviations that can harm the Target Households with reference to the 6 Right , namely the right target , the right amount , the right price , the right time , the right administration and right quality , so that the basic purpose of the program can be achieved with good Raskin . Furthermore, the Raskin program execution at the point or distribution point should be no supervision of the competent authorities in order to ensure that the delivery of aid to the poor rice Target Households Beneficiaries actually refers to the 6 Right Keywords :Distribution, Rice Poor, and Poor Families.